A 3. A holiday house on the island of Gasparee, Trinidad - (:unkn) unknown (My University, 2010)
Description printed on the back of the postcard: "Numerous houses of this type are available for rent for short or long periods on the islands of the Gulf of Paria. They provide good bathing and fishing and are in frequent communication with Port-of-Spain by Government steamer."
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Vacation homes--Trinidad and Tobago; Boats and boating--Trinidad and Tobago; Gasparee; Gaspar Grande